Optimal timing of doses of chenic acid in patients with gall stones. Issue 6168 (7th April 1979) - Maudgal, D P; Bird, R; Northfield, T C
Abstract : Sixteen patients with gall stones were treated with chenic acid (14-16 mg/kg/day) given at three different times in random order for one month each. Before treatment the mean (+/- SE of mean) cholesterol saturation index (SI) of fasting gall-bladder bile was 1.28 +/- 0.06. During bedtime administration of chenic acid the mean SI fell to 0.78 +/- 0.04, which was significantly lower than that obtained with administration in the morning (0.92 +/- 0.05) or with three divided doses at mealtimes (0.92 +/- 0.04). The bile remained supersaturated in seven patients when they received a single morning dose, in five patients when they received mealtime doses, but in only one patient when a single bedtime dose was given. There was no significant difference in side effects between the three different dose timings, or in the proportion of bile acids present in the bile as chenic acid. This enhanced effect obtained with bedtime administration may be due to the enterohepatic circulation of bile acids being maintained during overnight fasting.